SOCIO-PSYCHOLOGICAL CAUSES OF SUICIDE: A THEORETICAL ANALYSIS - Odiljon Sadilloyev (Modern World Education: New Age Problems – New solutions, 2026)
This article provides a theoretical analysis of the socio-psychological causes of suicide. It examines the interplay between social integration, family environment, cognitive and emotional factors, peer influence, and life stressors in shaping suicidal behavior. The paper draws upon classical sociological frameworks (Durkheim), attachment theory (Bowlby), cognitive theory (Beck), and contemporary interpersonal models (Joiner) to explain how social, psychological, and relational dynamics contribute to vulnerability. The role of protective factors and resilience in prevention strategies is also discussed, emphasizing the importance of supportive relationships, emotional regulation, and community interventions.